Relationship between academic staff withdrawal behaviours and administrative effectiveness of heads of department of universities - Azelama, Beauty Avoedoya; Osumah, Obaze Agbonluae (Universitas Negeri Padang, 2022)
The study examined the relationship between withdrawal behaviours and administrative effectiveness of heads of academic departments of the universities in Edo State Two research questions were raised and two hypotheses were formulated to guide the study. The study adopted the combination of survey method and correlational research design. A sample of 1,100 representing 40 percent of the population was drawn using the multi-stage stratified random sampling technique. The instruments used for the study were Absenteeism of Academic Staff (AASS) and Instrument for Measuring Lateness of Academic Staff (MLASS) and Head of Department Administrative Effectiveness Questionnaire (HODAEQ). Cronbach Alpha reliability was used to determine the reliability of the instruments. Hypotheses 1 and 2 were tested, using the Pearson Product Moment Correlation Co-efficient. The results of the study showed that: there was a strong, inverse and significant relationship between academic staff absenteeism and administrative effectiveness of the Heads of Department. The study also found that there was a strong, inverse and significant relationship between academic staff, lateness and administrative effectiveness of the heads of department. It was therefore concluded that absenteeism and lateness withdrawal behaviour of academic staff has adverse effect on HOD’s administrative effectiveness. The study consequently recommended among others staff enlightenment on the adverse impact of Academic Staff withdrawal behaviours on Heads of Departments’ administrative effectiveness.